Kamus dan Fungsinya Dalam Pembelajaran Bahasa Arab - Marisa Saputri; M,Taufik Hidayat; Nandang Sarip Hidayat (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2024)
This research aims to explore the role of dictionaries in learning Arabic, particularly in facilitating vocabulary comprehension for learners and enthusiasts of the Arabic language. The study employs a qualitative method with a library research approach. Data collection techniques are carried out through literature reviews and documentation studies. The collected data is analyzed using a descriptive analysis method, followed by drawing conclusions. The results of this study indicate that dictionaries have various terminologies in Arabic, such as mu’jam, fihris, and mau’suah. These terms refer to books that contain a large number of vocabulary words, along with explanations, interpretations, or elucidations of the meanings of each word. The content of dictionaries is organized according to specific systems, either based on the order of the Arabic alphabet (phonetics) or thematic categories (meanings). In terms of function, dictionaries play a significant role in Arabic language learning. They help clarify word meanings, facilitate the process of language translation, enrich learners’ vocabulary, and deepen understanding of Arabic texts. Thus, the use of dictionaries can enhance the effectiveness and efficiency of learning the Arabic language. This study emphasizes that dictionaries are essential tools that not only serve as sources of information but also as means for developing language skills among Arabic language learners.